Penerepan Media Pembelajaran Articulate Storyline pada Model Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VII SMPN 2 Sungguminasa - Alifah Dhiah Qanifah Lestari; Salma Samputri; Nurhayani H. Muhiddin (Celebes Science Education, 2024)
This study aims to determine: (1) the level of learning outcomes of students before and after the application of Articulate storyline media assisted by the Discovery learning model (2) the increase in learning outcomes of VII grade students of SMPN 2 Sungguminasa who are taught by applying Articulate storyline learning media assisted by the Discovery learning model (3) the application of Articulate storyline learning media assisted by the Discovery learning model can improve the learning outcomes of VII grade students of SMPN 2 Sungguminasa on the material of the Solar system. This type of research is One Group Pretest-Posttest Design research. The population of this study were all seventh grade students of SMPN 2 Sungguminasa. The sample was selected by purposive sampling technique and obtained the experimental class VII.4 with a sample size of 31. The research instrument used was a learning outcome test question. Data collection techniques in this study by giving pretest and posttest. Data were analyzed with descriptive statistics and inferential statistical analysis. The results of descriptive statistical analysis of pretest student learning outcomes were in the low category with an average pretest score of 6.29 and the posttest average was in the high category with an average posttest score of 13.93. The increase in student learning outcomes is in the medium category with an N-gain score of 0.56. The results of inferential statistical analysis showed that there was a significant increase in the average value of student learning outcomes after the application of Articulate Storyline media assisted by the Discovery learning model.